Acceptability and Antioxidant Activity Level of Shredded Banana Flower-Chicken Meat - Novidiyanto Novidiyanto; Ori Pertami Enardi; Ade Devriany; Auronita Puspa Pratiwi; Musrifa Airuni (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
Background: Data Riskesdas 2013 shows that the average amount portion of vegetable consumption in people aged 10 years or older is only 0.5 portions while the vegetable consumption category is said to be